Multimorbidity in Children and Youth Across the Life-course (MY LIFE): protocol of a Canadian prospective study - Michael Boyle; Mark A Ferro; Brian Timmons; Ellen L Lipman; Ryan J Van Lieshout; Jan Willem Gorter; Lilly Shanahan; Kathy Georgiades (BMJ Open)
Introduction Multimorbidity, the co-occurrence of a chronic physical condition and mental disorder, affects a substantial number of children and youth and can lead to compromised quality of life, hardship for families, and an increased burden on the healthcare system. We are conducting a study to document the course of mental disorder in children and youth diagnosed with a chronic physical condition; identify predictors of child and youth multimorbidity; examine whether the effects of these predictors are moderated by relevant psychosocial and biological factors; explore potential inflammatory and stress biomarkers that mediate the onset of child and youth multimorbidity; and, assess whether multimorbidity in children and youth alters patterns of mental health service use.Methods and analysis Multimorbidity in Children and Youth Across the Life-course (MY LIFE) is a prospective study. Two hundred and fifty children and youth aged 2–16 years diagnosed with a chronic physical condition along with one parent will be recruited from the outpatient clinics at a paediatric tertiary care centre. Data will be collected using a multi-informant, multimethod design at four time-points (at recruitment, and at 6, 12 and 24 months postrecruitment). Parents will provide reports for all children/youth. In addition, youth ≥10 years will self-report. Mental disorder will be assessed using structured interviews. On completion of data collection, participant-reported data will be linked to provincial health records to identify mental health services use. Multilevel analyses (survival, proportional hazard, structural equation modelling) will be used to address MY LIFE objectives.Ethics and dissemination This study has been approved by the University of Waterloo Human Research Ethics Board and the Hamilton Integrated Research Ethics Board. Findings will be disseminated to key stakeholders using a number of outlets (peer-reviewed publications and conferences, lay informational pamphlets, social media).